Emergent patterns and processes in urban hydrocarbon governance. (December 2017) - Fry, Matthew; Brannstrom, Christian
Abstract: Beginning in the 2000s, the Dallas-Fort Worth metropolitan region became home to the world's largest and longest experiment in urban shale gas production, with 25, 182 drilling permits issued from 2000 to 2016 in the Barnett Shale. Urban hydrocarbon governance centered on establishing statutory setback distances between drilling sites and nearest houses or other protected uses. Here we analyze qualitative interview data obtained with a rigorous sampling frame to examine processes and outcomes of municipal-level hydrocarbon governance. We find that early municipal responses (2001–2002) revealed lack of technical expertise to respond to unconventional drilling and production. Controversial wells, which residents considered too close to houses, focused governance debates in several municipalities. Municipal policymakers reported that protecting public health and safety were top priorities in determining setbacks. After 2003, policymakers copied ordinance language from neighboring municipalities and established task forces and working groups to reduce political tensions. The role of the hydrocarbon industry included frequent claims seeking to exploit the longstanding separation of mineral and property estates, which encouraged municipalities to reduce setbacks and lower potential exposure to regulatory takings lawsuits. Over time, municipal regulatory power in hydrocarbon governance decreased while industry power increased, offering several implications for corporate responsibility and social license debates. Highlights: Rapid expansion of Barnett Shale drilling into city territories necessitated policy responses. We examine setback distance governance processes for the 2002–2015 period among cities. Key stakeholder interviews reveal how city governments created, copied, and revised ordinances. Governance involved competing imperatives among city governments, residents, and firms. Policy implications include greater attention to corporate social responsibility strategies.